Association of Xmn I Polymorphism and Hemoglobin E Haplotypes on Postnatal Gamma Globin Gene Expression in Homozygous Hemoglobin E - Supachai Ekwattanakit; Yuwarat Monteerarat; Suchada Riolueang; Kalaya Tachavanich; Vip Viprakasit (Advances in Hematology)
Background and Objectives. To explore the role of cis-regulatory sequences within the β globin gene cluster at chromosome 11 on human γ globin gene expression related to Hb E allele, we analyze baseline hematological data and Hb F values together with β globin haplotypes in homozygous Hb E. Patients and Methods. 80 individuals with molecularly confirmed homozygous Hb E were analyzed for the β globin haplotypes and Xmn I polymorphism using PCR-RFLPs. 74 individuals with complete laboratory data were further studied for association analyses. Results. Eight different β globin haplotypes were found linked to Hb E alleles; three major haplotypes were (a) (III), (b) (V), and (c) (IV) accounting for 94% of Hb E chromosomes. A new haplotype (Th-1) was identified and most likely converted from the major ones. The majority of individuals had Hb F < 5%; only 10.8% of homozygous Hb E had high Hb F (average 10.5%, range 5.8–14.3%). No association was found on a specific haplotype or Xmn I in these individuals with high Hb F, measured by alkaline denaturation. Conclusion. The cis-regulation of γ globin gene expression might not be apparent under a milder condition with lesser globin imbalance such as homozygous Hb E.